2020
DOI: 10.1002/cncy.22271
|View full text |Cite
|
Sign up to set email alerts
|

Cytologic grading of primary malignant salivary gland tumors: A blinded review by an international panel

Abstract: BACKGROUND: Fine needle aspiration (FNA) is commonly used for the preoperative evaluation of salivary gland tumors.Tumor grade is a key factor influencing clinical management of salivary gland carcinomas (SGCs). To assess the ability to grade nonbasaloid SGCs in FNA specimens, an international panel of cytopathologists convened to review and score SGC cases. METHODS: The study cohort included 61 cases of primary SGC from the pathology archives of 3 tertiary medical centers. Cases from 2005 to 2016 were selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 61 publications
0
29
0
Order By: Relevance
“…2 Although FNAC generally demonstrates good sensitivity (approximately 70%-80%) and high specificity (>90%) for diagnosing malignancy among patients with neoplastic lesions, these test characteristics have shown wide heterogeneity across institutions. 2,3 Salivary gland FNAC also may distinguish low-grade from high-grade malignancy, 4 which can alter the surgical approach from a limited excision to a radical resection, with the potential for facial nerve sacrifice and ipsilateral neck dissection. 4 However, in the last several years, the interinstitutional variability in salivary gland FNAC performance combined with the less than perfect sensitivity for malignancy has led to increasing interest in a universal risk stratification system for salivary gland FNAC classification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Although FNAC generally demonstrates good sensitivity (approximately 70%-80%) and high specificity (>90%) for diagnosing malignancy among patients with neoplastic lesions, these test characteristics have shown wide heterogeneity across institutions. 2,3 Salivary gland FNAC also may distinguish low-grade from high-grade malignancy, 4 which can alter the surgical approach from a limited excision to a radical resection, with the potential for facial nerve sacrifice and ipsilateral neck dissection. 4 However, in the last several years, the interinstitutional variability in salivary gland FNAC performance combined with the less than perfect sensitivity for malignancy has led to increasing interest in a universal risk stratification system for salivary gland FNAC classification.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Salivary gland FNAC also may distinguish low-grade from high-grade malignancy, 4 which can alter the surgical approach from a limited excision to a radical resection, with the potential for facial nerve sacrifice and ipsilateral neck dissection. 4 However, in the last several years, the interinstitutional variability in salivary gland FNAC performance combined with the less than perfect sensitivity for malignancy has led to increasing interest in a universal risk stratification system for salivary gland FNAC classification. 5,6 The Milan System for Reporting Salivary Gland Cytopathology (MSRSGC) was introduced to address these issues, creating a standardized system with which to improve the practicing cytologist's diagnostic approach and better guide subsequent therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Miller et al reported high diagnostic accuracy for MEC (78.7%) and a higher ROM when MEC is included in the differential diagnosis 34 . Johnson et al also reported high diagnostic accuracy for MEC but their study only included neoplastic lesions and the best overall agreement among the panelists was noted with regard to high‐grade lesions 35 . In the current study, the majority of MECs were low grade (10 of 11 cases) and were classified in the indeterminant categories (AUS, SUMP, or suspicious).…”
Section: Discussionmentioning
confidence: 99%
“…From a clinical perspective, HGT is known to impart more aggressive biologic behavior and a worse prognosis than conventional low‐ to intermediate‐grade SGC 4,6‐8 . Preoperative recognition of a high‐grade component by fine needle aspiration (FNA) would therefore be useful for patient prognostication as well as for influencing patient management, including presurgical planning 9 . Despite wide recognition of this disease concept, only a few case reports describing the cytological features of SGC with HGT have been published, 10‐17 and comprehensive FNA case series are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…4,[6][7][8] Preoperative recognition of a high-grade component by fine needle aspiration (FNA) would therefore be useful for patient prognostication as well as for influencing patient management, including presurgical planning. 9 Despite wide recognition of this disease concept, only a few case reports describing the cytological features of SGC with HGT have been published, [10][11][12][13][14][15][16][17] and comprehensive FNA case series are lacking. Using a multi-institutional approach, we describe the clinical and cytomorphologic features of the largest FNA series of SGC with HGT and provide a comprehensive review of the literature.…”
Section: Introductionmentioning
confidence: 99%